The effectiveness of lifestyle adaptation for the prevention of prediabetes in adults: a systematic review - Shaw, Ian (Hindawi Publishing Corporation, 2017)
Diabetes prevalence is increasing exceptionally worldwide and with this come associated healthcare costs. The primary outcome of this systematic review was to assess glycaemic control and incidence of Type 2 diabetes mellitus (T2DM) diagnosis after exercise and dietary intervention (measured with any validated scale). The secondary outcome assessed body mass index change, weight change, and physical exercise capacity after diet and exercise intervention (measured with any validated scale). 1,780 studies were identified from searching electronic databases. Relevant studies went through a selection process. The inclusion criteria for all studies were people with prediabetes diagnosed by either impaired glucose tolerance (IGT) or impaired fasting glucose (IFG). Lifestyle adaptation reduced the incidence of diabetes development more than standard treatment. Furthermore, better glycaemic control, improved physical exercise capacity, and increased weight reduction were observed with lifestyle intervention over standard treatment. Finally, improvements over the long term deteriorated, highlighting problems with long-term adherence to lifestyle changes. Overall, cumulative incidence of diabetes is drastically reduced in the intervention groups compared to control groups (standard care). Furthermore, glycaemic control was improved in the short term, with many participants reverting to normoglycaemia.